CheX Is a Phosphorylated CheY Phosphatase Essential for Borrelia burgdorferi Chemotaxis - Motaleb, M. A. (American Society for Microbiology, 2005)
Motility and chemotaxis are believed to be important in the pathogenesis of Lyme disease caused by the spirochete Borrelia burgdorferi. Controlling the phosphorylation state of CheY, a response regulator protein, is essential for regulating bacterial chemotaxis and motility. Rapid dephosphorylation of phosphorylated CheY (CheY-P) is crucial for cells to respond to environmental changes. CheY-P dephosphorylation is accomplished by one or more phosphatases in different species, including CheZ, CheC, CheX, FliY, and/or FliY/N. Only a cheX phosphatase homolog has been identified in the B. burgdorferi genome. However, a role for cheX in chemotaxis has not been established in any bacterial species. Inactivating B. burgdorferi cheX by inserting a flgB-kan cassette resulted in cells (cheX mutant cells) with a distinct motility phenotype. While wild-type cells ran, paused (stopped or flexed), and reversed, the cheX mutant cells continuously flexed and were not able to run or reverse. Furthermore, swarm plate and capillary tube chemotaxis assays demonstrated that cheX mutant cells were deficient in chemotaxis. Wild-type chemotaxis and motility were restored when cheX mutant cells were complemented with a shuttle vector expressing CheX. Furthermore, CheX dephosphorylated CheY3-P in vitro and eluted as a homodimer in gel filtration chromatography. These findings demonstrated that B. burgdorferi CheX is a CheY-P phosphatase that is essential for chemotaxis and motility, which is consistent with CheX being the only CheY-P phosphatase in the B. burgdorferi chemotaxis signal transduction pathway.